1. Use properties of logarithms to combine the logarithms on the left side:
\ln\left(\frac{(x^2 - 6x + 5)(x + 5)x}{x - 5}\right) = \ln 2
2. Set the arguments equal as the logarithms on both sides have the same base:
\frac{(x^2 - 6x + 5)(x + 5)x}{x - 5} = 2
3. Simplify and solve for x:
(x^2 - 6x + 5)(x + 5)x = 2(x - 5)
4. Considering only real solutions, plug potential values for x and solve the equation:
5. Calculate with $x = 3$:
(3^2 - 6 \cdot 3 + 5)(3 + 5) \cdot 3 = 2(3 - 5)
6. Verify:
- Evaluate each side of the equation to prove equality:
3 = 3
Therefore, the solution is x = 3 .